Jurnal Pengembangan Sistem Informasi Travel Agent Sembalun Lombok Berbasi Website - Fajar Guritna Ananto Putra (The Indonesian Journal of Computer Science Research, 2023)
Website is an internet service that can display multimedia in the form of data, text, still or moving images, animation, sound, video, or a combination of all of them, both dynamic and static, which forms an interconnected series where each one is connected to one other. web pages (hyperlinks). The website itself has many benefits, one of which is to promote tourism in an area and country because it can provide benefits for its supporting infrastructure. Through this approach, it is hoped that information about tourism in Sembalun Lombok and its supporting infrastructure such as lodging, tourism, arts & culture. This website uses WordPress because it is easy to customize and there are many themes to choose from. The information displayed in the Sembalun Lombok tourism information system is expected to provide information to the public or tourists who want to visit Sembalun Lombok.